A study of prevalence of iron deficiency anaemia in infants and toddlers (6-24 months) by measuring serum ferritin levels - Chanpura, Vaishali R.; Shah, Nilesh T. (International Journal of Contemporary Pediatrics, 2019)
Background: Nutritional anemia is a worldwide problem with the highest prevalence in the developing countries. One of the most vulnerable groups is 6-24 months of age. NFHS-3 survey shows that the incidence of anemia in children aged 6-35 months is 79.2% with 72.7% in urban areas and 81.2% in rural areas. First stage of iron deficiency is depletion of iron stores, which is reflected by decreased serum ferritin levels and increased total iron binding capacity (TIBC) levels. The objective of this study was to detect presence of iron deficiency in children even before clinical appearance of anemia by measuring serum ferritin levels. Methods: The study was conducted from March 2017 to November 2017 in the Department of Pediatrics of Sir Sayajirao Gaekwad General Hospital, a tertiary level hospital and government medical college, Vadodara. A cross sectional study was done in which a total of 111 asymptomatic infants and toddlers in age group of 6-24 months presenting to well-baby clinic were enrolled randomly. Haemoglobin, RBC indices and serum ferritin levels were estimated. The children were classified into mild, moderate and severe anaemia according to their haemoglobin levels. Correlation with their serum ferritin levels was carried out by using statistical analysis. Results: Prevalence of anaemia (Hb <11gm/dl) was 84.14% in 6-12 months age group, 81.25% in 13-18 months age group and 84.61% in case of 19-24 months age group. Overall 83.78% of infants and toddlers were found to be anemic among 6-24 months age group. 55 infants (49.54%) among 111 infants had mild anaemia, 29 infants (26.12%) had moderate anaemia, 9 infants (8.1%) had severe anaemia. Majority of children (87 of 111 infants) had microcytic and hypochromic RBCs in their peripheral smear examination. 78 infants (72.07%)) had low serum Ferritin levels while only 31 infants had normal ferritin levels which is statistically significant (p=0.0084). Out of these, 4 infants had normal hemoglobin level. Conclusions: Anaemia is highly prevalent in the age group of 6 to 24 months even in otherwise healthy infants. Serum ferritin level is a good indicator of iron deficiency in children.